Zum morphologischen Bau und zur funktionellen Bedeutung der Ocellen der Libellen (Odonata). - Münchberg, Paul (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The ocelli of the Odonata form a triangle in the vertex region. The apertures of the larger median frontal eye of Anisoptera open in the main direction of flight and those of their smaller lateral ocelli open sideways, while the ocellus lenses of Zygoptera look in a more upward direction. Apart from the Gomphidae, the ocellus triangle of the great dragon-flies is compressed in space and consequently has a reduced incidence of light, which must have a favourable influence, however, on the perception of light in the direction of flight. The larger dimensions of the frontal eyes of Anisoptera, which certainly are connected with a greater degree of differentiation of the structural elements of the retina, are seen in relation with the better flight performance of the great dragon-flies. The fact that the median ocelli of Anisoptera, which tend to fly in twilight, are especially large, confirms their interpretation as "receptors for light of low intensity". The results of behavioural experiments suggest that the ocelli of dragon-flies also have the function of both phototactic and photokinetic stimulation. Their arrangement in space and dimension indicates that they inform also of the direction of the incident light rays.